Low‐cost soil CO2 efflux and point concentration sensing systems for terrestrial ecology applications. Issue 11 (21st July 2015) - Harmon, Thomas C.; Dierick, Diego; Trahan, Nicole; Allen, Michael F.; Rundel, Philip W.; Oberbauer, Steven F.; Schwendenmann, Luitgard; Zelikova, Tamara J.
Summary: Measuring CO2 concentrations and fluxes is key to the evaluation of terrestrial ecosystem carbon dynamics. Both the high cost and low portability of currently available sensors and field instruments are constraints to achieving adequate spatial and temporal coverage in characterizing ecosystem CO2 fluxes and point concentrations. We used commercially available, low‐cost and low‐power non‐dispersive infrared (NDIR) CO2 sensors to develop: (i) a soil CO2 efflux system (K‐33 ELG sensor, 0–1% or 10 000 ppm(v)) and (ii) a point CO2 concentration system (K‐33 BLG sensor, 0 to 30% or 300 000 ppm(v)). We first calibrated the sensors against benchmark instruments (LI‐COR LI‐6400 efflux system and Vaisala GMP343 probe). The K‐33 ELG sensor tracked the LI‐6400 well during a steady reduction from ˜ 4000 ppm to background CO2 levels (RMSE = 176 ppm). The K‐33 BLG point sensor were less favourable (RMSE = 424 ppm) because of its broad range of detection, but were suitable for proof‐of‐concept testing at elevated CO2 levels (> 1500 ppm). In field tests of soil CO2 efflux on locations with and without leaf litter, the K‐33 efflux system yielded mean surface efflux rate values significantly lower (by ˜ 27%) than those obtained with a LI‐COR LI‐6400 for the bare ( P = 0·006) and litter ( P = 0·002). We explain the systematic difference in terms of flux chamber geometry and potential leakage from the prototypical system. In a test on leaf cutter ant nest vents, the K‐33 BLG point system yielded comparable spatial and temporal patterns and slightly higher (˜ 10–15%) CO2 concentrations in comparison with a Vaisala GMP343 probe. The results provide proof‐of‐concept for the use of two low‐cost, portable CO2 sensing systems to enable terrestrial ecologists to substantially improve the characterization of CO2 fluxes and concentrations in heterogeneous environments.